Advances in Eucommia ulmoides polysaccharides: extraction, purification, structure, bioactivities and applications - Sun, Yanping; Zhang, Yuping; Sun, Minghao; Gao, Wuyou; He, Yujia; Wang, Yu; Yang, Bingyou; Kuang, Haixue (Frontiers in Pharmacology, 2024)
Eucommia ulmoides (EU) is a precious tree species native to China originating during the ice age. This species has important economic value and comprehensive development potential, particularly in medicinal applications. The medicinal parts of EU are its bark (Eucommiae cortex) and leaves (Eucommiae folium) which have been successively used as a traditional Chinese medicine to treat diseases since the first century BC. During the last 2 decades, as natural polysaccharides have become of increasing interest in pharmacology, biomedicine, cosmetic and food applications, more and more scholars have begun to study polysaccharides derived from EU as well. EU polysaccharides have been found to have a variety of biological functions both in vivo and in vitro, including immunomodulatory, antioxidant, anti-inflammatory, anticomplementary, antifatigue, and hepatoprotective activities. This review aims to summarize these recent advances in extraction, purification, structural characteristics, pharmacological activities and applications in different fields of EU bark and leaf polysaccharides. It was found that both Eucommiae folium polysaccharides and Eucommiae cortex polysaccharides were suitable for medicinal use. Eucommiae folium may potentially be used to substitute for Eucommiae cortex in terms of immunomodulation and antioxidant activities. This study serves as a valuable reference for improving the comprehensive utilization of EU polysaccharides and further promoting the application of EU polysaccharides.